2022
DOI: 10.3390/ijerph192113844
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exposure to Simulated Nocturnal Train Noise Leads to Impaired Sleep Quality and Endothelial Dysfunction in Young Healthy Men and Women: A Sex-Specific Analysis

Abstract: A series of human field studies demonstrated that simulated nocturnal traffic noise exposure impaired sleep quality and endothelial function, which could be significantly improved after intake of vitamin C in case of endothelial function. However, it remains unclear whether these changes follow a sex-specific pattern. Thus, we aimed to analyze the effect of simulated nocturnal train noise exposure on sleep quality, endothelial function and its associated changes after vitamin C intake, and other hemodynamic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…The authors demonstrated in men who were exposed to higher levels of traffic noise (> 55 dB) compared to men who were exposed to lower traffic noise levels (< 30 dB) that sleep duration was significantly reduced by 1.5 h. Conversely, there was no effect of higher traffic noise exposure on sleep duration in women. Sex-differences in noise sensitivity may further arise from a recent study in which we demonstrated that a significant improvement of endothelial function after train noise exposure and subsequent vitamin C intake only occurred in women, although there was no difference in case of train noise-induced impaired sleep quality and endothelial dysfunction ( 37 ). This suggests that there may be differences in mechanisms causing endothelial dysfunction between men and women.…”
Section: Discussionmentioning
confidence: 90%
“…The authors demonstrated in men who were exposed to higher levels of traffic noise (> 55 dB) compared to men who were exposed to lower traffic noise levels (< 30 dB) that sleep duration was significantly reduced by 1.5 h. Conversely, there was no effect of higher traffic noise exposure on sleep duration in women. Sex-differences in noise sensitivity may further arise from a recent study in which we demonstrated that a significant improvement of endothelial function after train noise exposure and subsequent vitamin C intake only occurred in women, although there was no difference in case of train noise-induced impaired sleep quality and endothelial dysfunction ( 37 ). This suggests that there may be differences in mechanisms causing endothelial dysfunction between men and women.…”
Section: Discussionmentioning
confidence: 90%
“…For example, exposure to loud noise and noise annoyance act as stressors, activating the autonomic nervous system and triggering the release of stress hormones, leading to physiological changes that can trigger AF in susceptible individuals. 116 In studies involving healthy individuals and patients with CVD, short-term exposure to simulated aircraft and railway noise has been found to impair sleep quality and increase stress hormone levels, blood pressure, endothelial dysfunction, and oxidative stress, 116,117 all of which have been linked with AF risk.…”
Section: Mechanistic Insights Linking the Exposome And Afmentioning
confidence: 99%
“…По результатам исследования FMD была значительно нарушена после ночей Noise 30 и Noise 60 как у мужчин, так и у женщин (p<0,001 по сравнению с контролем). С целью улучшения эндотелиальной функции пациентам давали витамин С, однако имело необнозначные результаты и давало положительный эффект только у женщин [78].…”
Section: уровень шумаunclassified